Political and Institutional Approaches to Advancing International Religious Freedom in the U.S. Foreign Policy in 1998–2020 - V. A. Shchipkov (Vestnik MGIMO-Universiteta)
The article traces the institutional and political evolution of the US implementing its concept of international religious freedom from 1998 to 2020. The concept became popular after the end of the Cold War when the defense of religion against socialistatheist ideas had lost its relevance due to political (the collapse of the Eastern bloc) and cultural (the growing importance of religion in many non-Western countries of the world) reasons. The article starts by reviewing the history of the emergence and development of the institutional infrastructure (legal acts, administrative entities, public and political organizations, think tanks, expert platforms, interdepartmental coordination formats, human rights projects, funding and grant programs, and new international organizations) that supported the US foreign policy advancing international religious freedom. The article divides the reconstruction of this process into two periods formed by adopting two acts: in 1998 — the International Religious Freedom Act, and in 2016 — the amendment to this Act named after congressman Frank Wolf. The study concludes that over the past twenty years, religion has finally developed as an independent track of the US foreign policy, although it has been developing inconsistently and has undergone repeated corrections. The concept of international religious freedom has become the ideational basis of this track, while the extensive institutional and political infrastructure serves as its apparatus. More than 80 percent of the world's population encounters religious persecution. It legitimizes the concept, which encourages widespread support for religious minorities as opposed to the religious majority, and opens the way for the US to build sustainable ties with religious communities and their leaders worldwide, allowing them to influence political processes in different regions. The US has recently promoted the integration of this policy track into international institutions, establishing the International Religious Freedom or Belief Alliance.